Ion-Pair Extraction Spectrophotometric Determination of Trace Amounts of Chloramphenicol - Sheibani, M.; Parham, H.; Yahyazadeh, A. (Asian Journal of Chemistry, 2010)
A simple, sensitive and selective extraction-spectrophotometric method for the determination of trace amounts of chloramphenicol is reported. The chloramphenicol-alizarine yellow ion-pair in acidic media is quantitatively extracted into carbon tetrachloride and its absorbance is measured at 390 nm at room temperature. The effect of different variables such as solvent, volume of extracting solvent, volume of anionic reagent, pH, ionic strength (NaCl 0.1 M) and shaking time is investigated and optimum conditions for quantitative extraction of chloramphenicol is obtained. Linear calibration graph over the chloramphenicol concentration range of 0.03-4.00 μg mL-1 and regression coefficient of 0.9999 is obtained. The relative standard deviation of 10 replicate determination of 2 μg mL-1 of chloramphenicol is 1.95 %. Limit of detection of the method is 0.022 μg mL-1. The method is used for determination of chloramphenicol in 250 mg capsules and 0.5 % drops and also 150 mg/5 mL of suspension and good results are obtained.